Computational modeling of specific biological structures behavior - Lemic, A.M., Shool of Dentistry, Belgrade (Serbia); Tihacek-Sojic, Lj., Shool of Dentistry, Belgrade (Serbia); Ilic, J., Shool of Dentistry, Belgrade (Serbia); Zivkovic, R., Shool of Dentistry, Belgrade (Serbia) (Acta veterinaria (Beograd), 2006)
The aim of this paper was to present computational modeling of any (human or animal) intact tooth behavior under loading and evaluate of intact tooth stress and strain distribution pattern. For the investigation to be carried out a mathematical model of an intact tooth had to be created. This paper offers the new approach in veterinary dental scientific research. Once when a mathematical model is made, it is possible by changing the parameters to investigate different clinical situation. With increasing popularity of veterinary dentistry, the FEM/computational analyses could became a usual tool in biomechanical veterinary dental research due to its noninvansiveness.